THE RELATIONSHIP BETWEEN INTENSITY OF SOCIAL MEDIA USE AND HEDONIC LIFESTYLE IN ADOLESCENTS - Fikhi Amana; Maryam, Effy Wardati (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to determine the relationship between the intensity of social media use and the hedonic lifestyle of teenagers SMP X at Sidoarjo, with a sample population of 600 students. Method: The sample in this study was 221 with the sample determined according to strata which was then calculated using the 5% error rate table from Isac & Michael, with an average age of 13-16 years. This research uses an accidental sampling method and uses a psychological scale to measure hedonic lifestyle and intensity of social media use. To test the hypothesis, use Pearson product moment correlation analysis. Results: This research found that there was a relationship between the intensity of social media use and the hedonic lifestyle of teenagers SMP at Sidoarjo with an effective contribution of 84.1% as indicated by a correlation coefficient of r = 0.918 and a significance level of p = 0.000 (<0.05). It can be concluded that a hedonic lifestyle occurs more often in teenagers who use social media intensively, and vice versa. Novelty: This study highlights a strong positive correlation between social media intensity and hedonic lifestyle specifically among junior high school teenagers in Sidoarjo, providing quantitative insight (r = 0.918) into how digital behavior correlates with lifestyle patterns at a local educational level.